Effects of carbon nanotube content on morphology of SiCp(CNT) hybrid reinforcement and tensile mechanical properties of SiCp(CNT)/Al composites. Issue 7 (14th February 2017) - Li, Shisheng; Su, Yishi; Jin, Huiling; Huang, Yu; Ouyang, Qiubao; Zhang, Di
Abstract: Abstract : In this work, the high-performance silicon carbide particle SiCp[carbon nanotube (CNT)] hybrid reinforcement is currently explored to develop the advanced metal matrix composites. 17 wt% SiCp(CNT)/Al composites were fabricated by a powder metallurgy technique, in which SiCp(CNT) hybrid reinforcement with various CNT contents (e.g., 3, 6 and 9 wt%) were applied. Effects of CNT content on the morphology of SiCp(CNT) hybrid reinforcement, the microstructural characteristics, and the tensile mechanical behavior of SiCp(CNT)/Al composites were studied as well. Especially, the SiCp(CNT)/Al composites with 6 wt% CNT in SiCp(CNT) hybrid reinforcement exhibited the most significant enhancing effects in the elastic modulus and tensile strength. Meanwhile, the SiCp(CNT)/Al composites produced a synergistic strengthening effect of SiCp and CNT compared to SiCp/Al composites, while the SiCp(CNT)/Al composites with high CNT content in SiCp(CNT) hybrid reinforcement provided weak improvement in the tensile strength and ductility due to the forming agglomeration of CNT in the matrix.